Relationship between HER2 and clinicopathological data in gastric adenocarcinomas: HER2 status in gastric adenocarcinomas - Ceylan, Cengiz; Angin, Yavuz Selim; Baran, Necip Tolga; Kocaaslan, Hüseyin; Cengiz, Emrah; Güngörür, Omer; Güzel, Mehmet; Saglam, Kutay; Aydin, Cemalettin (Journal of Surgery and Medicine, 2023)
Background/Aim: The impact of human epidermal growth factor receptor 2 (HER2) overexpression on the surveillance of gastric cancer remains uncertain. Typically, HER2 status is assessed in both locally advanced and metastatic diseases, and targeted therapies are applied to cases with HER2-positive status. Our objective was to investigate the correlation between HER2 receptor status, clinicopathological characteristics, and prognosis in gastric cancers across all stages. Based on the results from this investigation, we aim to provide clinicians with insights into the clinicopathological conditions that warrant HER2 investigation. Methods: In this retrospective study, we conducted a comprehensive analysis of clinicopathological data from a cohort of 169 patients who underwent surgical treatment for gastric cancer between 2014 and 2022. The HER2 status was determined based on results from immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) techniques applied to gastric cancer pathology samples. Based on the HER2 positivity, the patients were classified into two distinct groups: (1) HER2-positive and (2) HER2-negative. The relationship between the clinicopathological variables, HER2 status, and overall survival (OS) was evaluated using chi-squared and Kaplan–Meier analyses. A statistical significance level of P <0.05 was applied to determine significant associations. Results: According to the IHC analyses performed in our study population, 33 among 169 patients were HER2-positive (19.53%). Statistically significant factors related to HER2 positivity, such as male gender (P=0.009), pathological stage, N category, lymphovascular invasion status ([LVI] P=0.046), and proximal tumor location (P=0.015) were observed. In addition, OS was 40.49 (6.21) months in HER2-positive gastric cancer patients and 57.43 (3.48) months in HER2-negative gastric cancers (P=0.045). Conclusion: Irrespective of the pathological stage, gastric cancer exhibited HER2 positivity at a ratio of 5:1. Among the clinicopathological findings, a significant correlation was observed between HER2 expression and gastric cancers characterized by aggressive features. Moreover, HER2 positivity was associated with an unfavorable prognosis in gastric cancer patients.